Evaluation of apolipoprotein A1, apolipoprotein b levels in the blood serum and their ratio in young adults with untreated somatotropic deficiency appeared in childhood - Ткачова, Тетяна Олександрівна; Вишневська, Ольга Анатоліївна; Большова, Олена Василівна (ScienceRise: Medical Science, 2016)
There was studied the content of apolipoproteins А1 (ApоА1) and apolipoproteins B (ApoВ) in the blood serum and their ratio in young adults ( mean age 22,47±0,30 years) with somatotropic deficiency, appeared in childhood. In most patients, who did not receive treatment with preparations of recombinant growth hormone (rGH) the undesirable changes of the lipid profile were established, especially the essential decrease of apolipoproteins A1 level and increase of apolipoproteins B level, disturbance of their ratio that favors the significant growth of cardiovascular risk. Aim. Determination of the presence of cardio-vascular risk factors in young adults with prolonged deficiency of growth hormone by the study of apolipoprotein А1, apolipoprotein В in the blood and their ratio. Methods. АpоА1 and АpоВ levels in the blood serum were determined by immunoturbidimetric method (Cobas 6000; RocheDiagnostics, Switzerland). The level of insulin-like growth factor (IGF) in the blood plasma was determined by radioimmunological method using the standard sets «IRMAIGF-1" («Immunotech» , Czech Republic). The measuring of height was carried out using stadiometer «SystemDr.KellerJ.», body mass was measured using electronic weigher Tanita BC587 (Japan). The bone age was determined by the atlas W. W. Greulich & S. P. Pyle (1993). The materials of Register of patients with somatotropic deficiency, created on the base of the department of child endocrine pathology of SI “Institute of endocrinology and metabolism, named after V. P. Komissarenko, NAMS of Ukraine” were used in the work. Statistical processing of the results was carried out using Microsoft Excel statistical programs with the help of methods of variation statistics. The results were presented as the mean values and their standard mistake (M±m). The assessment of statistical reliability was realized by Student parametric t-criterion. The difference between results was considered as a reliable one at р<0,05. Results of research. 174 patients with somatotropic deficiency, appeared in the childhood, were examined. Mean age was 22,47±0,30 years ( in women – 23,47±0,61 years; in men – 22,03±0,32 years). The height of patients was 138,0 – 174,0 cm, body mass index – from 19,2 to 33,3. Under conditions of prolonged deficiency of growth hormone only 17.8 % of patients had АpоА1 parameters within the norm and 67,2 % – the normal АpоВ parameters in the blood serum. The mean level of ApoA1 in the blood serum of young adults was reliably lower than the control parameters (0,88±0,014 g/l and 1,21±0,018 g/l respectively, p<0.001). At the same time the mean ApoB level essentially exceeded the parameters in the control group (1,171±0,022g/l and 0,995±0,028 g/l, respectively, p<0.001). ApoB / ApoA1 ratio exceeded the value 1 and was 1,366±0,028 (in the control group 0,816±0,016, p<0.001). The essential gender differences in parameters of АpоА1,АpоВ and АpоВ/АpоА1 in young adults with somatotropic deficiency, who did not receive treatment with rGH, were not found. Conclusion. There were established the significant undesirable changes of the levels of apolipoproteins А1, apolipoproteins B in the blood serum and disturbance of their ratio in young adults with somatotropic deficiency, appeared in childhood. The received data testify to the accumulation of cardiovascular risk factors in young adults under conditions of prolonged deficiency of growth hormones and the necessity of continuation/renewal of therapy with preparations of recombinant growth hormone